Pengaruh Penambahan Fly Ash pada Sifat Mekanik Beton Daur Ulang dengan Mutu Beton fc’ = 19.3 MPa - Diana Ningrum; Handika Setya Wijaya; Virginia Soares (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2021)
The development of development in Indonesia is increasing along with population growth, as a result of the increasing development, environmental aspects need to be considered, because the use of cement, sand and coral (gravel) which is taken from nature must be limited in its taking or use. So the researchers used recycled coarse aggregates (RCA), from the remaining test objects of the Tribhuwana Tunggadewi University Laboratory malang as a substitute for the use of part of the coarse aggregate with a variation of 0%, 75% and fly ash waste as a partial substitution of cement use, this fly ash functioned as a filter to fill the cavities in the RCA. The methods used are experimental methods and the tests carried out are compressive strength testing and bending strength testing with a treatment / curing period of 7 days. The results of the study were carried out with the addition of fly ash to RCA in terms of the results of compressive strength testing showing that the maximum compressive strength of concrete is in the variation of fly ash 20% against RCA 0% with an increase in compressive strength of 21,535 MPa while the minimum compressive strength is at a variation of fly ash 30% against RCA 75% of 13,501 MPa, the compressive strength of concrete experiences a significant decrease in compressive strength often the addition of fly ash variations due to the wear value of RCA which is quite high. When compared, the test results of bending strength, which was reviewed from the load-deflection relationship of fly ash variations of 0% and 20% against RCA 75% had a maximum P load of 2600 kg, with small deflection. Therefore, fly ash and RCA can be used as materials in concrete mixtures with certain variations.